Greater Neonatal Fat‐Free Mass and Similar Fat Mass Following a Randomized Trial to Control Excess Gestational Weight Gain. Issue 3 (21st February 2018) - Gallagher, Dympna; Rosenn, Barak; Toro‐Ramos, Tatiana; Paley, Charles; Gidwani, Sonia; Horowitz, Michelle; Crane, Janet; Lin, Susan; Thornton, John C.; Pi‐Sunyer, Xavier
Abstract : Objective: The objective of this study was to determine the effectiveness of controlling maternal gestational weight gain (GWG) in the second and third trimesters on neonate body composition. Methods: Two hundred ten healthy women with overweight (25 > BMI < 30) or obesity (BMI ≥ 30) were randomly assigned to a lifestyle intervention (LI) program focused on controlling GWG through nutrition and activity behaviors or to usual obstetrical care (UC). Infant fat and fat‐free mass (FFM) at birth were measured by using air displacement plethysmography (PEA POD) and by using quantitative magnetic resonance (QMR). Results: At baseline, there were no between‐group differences in maternal characteristics (mean [SD]): age: 33.8 (4.3) years, weight: 81.9 (13.7) kg, BMI: 30.4 (4.5), and gestational age at randomization: 14.9 (0.8) weeks. GWG was less in the LI group by 1.79 kg ( P = 0.003) or 0.0501 kg/wk ( P = 0.002). Compared with UC infants, LI infants had greater weight (131 ± 59 g P = 0.03), FFM (98 ± 45 g; P = 0.03) measured by PEA POD, and lean mass (105 ± 38 g; P = 0.006) measured by QMR. Fat mass and percent fat were not significantly different. Conclusions: Intervening in women with overweight and obesity through behaviors promoting healthy diet and physical activity to control GWG resulted in neonates with similar fat and greater FFM.